Differential effectiveness of group, individual, and conjoint treatments: An archival analysis of OQ-45 change trajectories. (2nd September 2016) - Burlingame, Gary M.; Gleave, Robert; Erekson, Davey; Nelson, Philip L.; Olsen, Joseph; Thayer, Steve; Beecher, Mark
Abstract: Objective : While empirically-supported treatment (EST) choices are continually expanding, choices regarding formats for delivery (individual only, group only, or conjoint [simultaneous individual & group]) are often determined by agency resources or clinician preference. Studies comparing individual and group formats have produced mixed results, while recent meta-analytic reviews support format equivalence.Method : We employed a multilevel model to test for outcome differences using the OQ-45 on an outpatient archival data set of clients receiving individual-only ( n = 11, 764), group-only ( n = 152) or conjoint ( n = 1557).Results : Individual and group outcomes were equivalent with some analyses showing conjoint trailing. Moderators of change included initial distress, treatment duration, intra-group dependency, and format.Conclusions : Results support meta-analytic findings of format equivalence in a naturalistic setting for group and individual. Referral practices and future results are discussed.